Aktivitas Anti-inflamasi Parem Instant Tradisional dari Bahan Usada Bali pada Mencit Inflamasi yang Diinduksi Karagenan - Putu Era Sandhi Kusuma Yuda; Gusti Ayu Putu Yosinta Sasmita; Erna Cahyaningsih (Fakultas Farmasi Universitas Pancasila, 2022)
The increase of adverse reactions from anti-inflammatory drugs that are used in the long term by rheumatic patients requires a relatively safer alternative therapy. This research was aimed to evaluate the effectiveness of Usada Bali's instant parem (BIO-PAREM) as an anti-inflammatory agent against carrageenan-induced inflammatory mice. The method used was randomized pre-test and post-test with control group design using 24 mice which were divided into 4 treatment groups. The negative control group was given a vehicle, the positive control group was given anti-inflammatory gel of diclofenac sodium, group 3 (P1) was given BIO-PAREM with a concentration of 12.5% and group 4 (P2) was given BIO-PAREM with a concentration of 25%. All groups were induced with 1% carrageenan, then the mice's paw edema volume was calculated using a plethysmometer at 0, 1, 2, 3, and 4 hours. The Kruskal Wallis and Mann Whitney test were used to analyse the relative change of inflammation volume. The BIO-PAREM phytochemical screening assay showed the presence of alkaloids, flavonoids, tannins, steroids and triterpenoids. BIO-PAREM showed significant inhibition of mice's paw edema at concentrations of 12.5% and 25% (p <0.05) indicating its potential as a candidate for topical alternative treatment for rheumatism.